Identification of Work Accidents at Nurse in General Hospital Langsa Area - Tengku Zulfah; Tri Niswati Utami; Nur Aini (Journal La Medihealtico, 2022)
The hospital as a service industry is an industry that has a variety of complex labor problems with various risks of occupational diseases and even work-related accidents according to the type of work, so hospitals are obliged to implement Hospital Occupational Health and Safety (K3RS) efforts. The purpose of this study was to identify the causes of work accidents at Langsa Hospital. This type of research is descriptive analytic with a qualitative approach. The informants in this study consisted of 5 people, namely 1 Hospital Director or deputy, 1 K3RS team leader, 1 head nurse and 2 nurses. The results showed that the K3 staff at the Langsa City Hospital had not all received special K3 training, the implementation of health promotion to nurses and K3 workers was not carried out comprehensively and continuously, nurses carried out their duties in accordance with the applicable Standard Operating Procedures (SPO), but not all nurses had discipline in carrying out their duties, nurses have attended training on the use of PPE, but not all nurses ensure that PPE functions properly and correctly. It is recommended that Langsa Hospital provide a special budget for the implementation of K3 in the hospital and facilitate all K3 personnel to have good competence and be firm, such as by giving sanctions to all nurses who do not carry out their duties and do not have a good work culture.